MODERN SURGICAL TREATMENT OF GAS GANGRENE (World Bulletin of Public Health, 2025)
Presented article displays the work, containing review and analysis of modern literature and textbooks, which contains the most important information about the gas gangrene – a dangerous infection of the battlefield, which could sometimes occur in a peaceful time